Implementasi Nilai-Nilai Pendidikan Akhlak dalam Al-Quran Surat Ali-Imran Ayat 159 - Nurseha, Afif; Syakir, Fuad (CV. Kalimasada Group, 2023)
This research is motivated by the emergence of the phenomenon of moral decline, especially among students. The existence of criminal acts, student delinquency, brawls, moral degradation is one of the many causes of moral decline. Realizing the importance of the position and function of the Al-Quran for mankind, its application is important and mandatory as a form of mutual concern, especially for educators, so that the values ​​of moral education included in it can be conveyed properly to the people, especially to students. Starting from this situation, the author is interested in examining the implementation of moral education values ​​in the Al-Quran Surah Ali-Imran verse 159 at SMPN 1 Pagaden. This research is a descriptive qualitative research, using a case study approach. The primary data source used is QS. Ali-Imran : 159 and the parties directly related to the discussion. While the secondary data is in the form of books, journal reports, articles and writings that talk about morality and the inculcation of moral education values. The results of the study show that, 1) The value of QS moral education. Ali-Imran: 159 is a gentle attitude, forgiving, deliberation and trust. 2) The teacher's role as a facilitator through advice, example, attention and habituation. 3) Factors that influence students' morals are the family environment, society and technology. 4) Obstacles faced by teachers are the lack of student motivation. 5) The role of schools is to provide the best facilities, professional educators and programs.